2004
DOI: 10.2172/919131
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic array performance model.

Abstract: This document summarizes the equations and applications associated with the photovoltaic array performance model developed at Sandia National Laboratories over the last twelve years. Electrical, thermal, and optical characteristics for photovoltaic modules are included in the model, and the model is designed to use hourly solar resource and meteorological data. The versatility and accuracy of the model has been validated for flat-plate modules (all technologies) and for concentrator modules, as well as for lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
190
0
34

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 559 publications
(224 citation statements)
references
References 17 publications
0
190
0
34
Order By: Relevance
“…where Isc h (h) is the mean hourly short-circuit current measured per each cell or module, POA is the mean hourly plane of array irradiance, h is the hour, j and k are the hours when the first and last current measurements are taken, and n is the number of hours used for the daily average. Where not available, the POA has been calculated using the hourly values of global horizontal irradiance and angle of incidence, by estimating the direct, the ground-reflected diffuse, and the sky-diffuse components of global horizontal irradiance [15][16][17][18]. The same filtering criteria applied in the previous work [12] have been used in the present study.…”
Section: Soiling Metricsmentioning
confidence: 99%
“…where Isc h (h) is the mean hourly short-circuit current measured per each cell or module, POA is the mean hourly plane of array irradiance, h is the hour, j and k are the hours when the first and last current measurements are taken, and n is the number of hours used for the daily average. Where not available, the POA has been calculated using the hourly values of global horizontal irradiance and angle of incidence, by estimating the direct, the ground-reflected diffuse, and the sky-diffuse components of global horizontal irradiance [15][16][17][18]. The same filtering criteria applied in the previous work [12] have been used in the present study.…”
Section: Soiling Metricsmentioning
confidence: 99%
“…The power generated by the PV array is not only dependent on the solar irradiation but also dependent on the ambient temperature of the site. A maximum power point tracker (MPPT) is often used in the PV array to reach the maximum output power at any radiation level [16,17]. The maximum output power at different radiation and temperature is calculated by the following equation:…”
Section: Estimating the Output Power Of Pv Arraymentioning
confidence: 99%
“…Many studies have showed that the active output of photovoltaic generators could be described as [30]:…”
Section: Output Uncertainty Of Photovoltaic Generatorsmentioning
confidence: 99%